Investigation of impurities in Supercritical Fluid Chromatography with Trapped Ion Mobility Spectrometry – Quadrupole / Time of Flight Mass Spectrometry - Synefakis,Evangelos (2025)
Introduction: Achieving and retaining a low background signal is essential for analytical techniques, especially for extremely accurate systems such as supercritical fluid chromatography (SFC) coupled with high-resolution mass spectrometry (HRMS) since the limits of detections are heavily dependent on the background signal. Background: A standard option to ensure a low background signal is the usage of ultrapure reagents. These reagents avoid contaminating the system and thus increase the background signal. In this study, an increase in the background signal was observed due to impurities originating from the CO2 cylinder or the CO2 pump. No prior literature has reported impurities originating from these sources. Thus, there is a lack of knowledge about what the contaminations are, what their properties are, and how they could be efficiently analyzed. Aims: This project aims to respond to the following questions: Do the impurities arise from the CO2 cylinder or the CO2 pump? Could the concentration of these impurities be related to the process of CO2 production? Is gas chromatography coupled with mass spectrometry (GC/MS) suitable for studying the structure and properties of these impurities? Methods: The experimental procedure was initialized by isolating the impurities in liquid solvent by flushing CO2 from the cylinder into the solvent over a week, and injecting samples at various timepoints in trapped ion mobility spectrometry hyphenated with quadrupole time of flight mass spectrometry (tims-TOF). The last aliquot was concentrated and injected into GC/MS, before and after derivatization and at different dilutions. Results: The aliquots collected showed that the background signal in tims-TOF increased with time while the GC/MS injections did not show any peaks for any of the samples injected. Conclusion: The results of this study suggest that the CO2 cylinder was the source of contamination, and that GC/MS is not suitable for their analysis, probably due to poor volatility or incapability to pass the wool of the liner. Additionally, no correlation between the concentration of these impurities and the period of CO2 production could be found in the literature.
Keywords: Contamination; Carbon Dioxide; Supercritical fluid chromatography; tims-TOF; Analytical chemistry